A new multi-component composite with gamma polyglutamic acid as corrosion and scale inhibitor. (June 2015) - Chen, Y.; Sun, C.; Huang, C.; Xu, H.; Wu, J.
Abstract : A new multi-component composite corrosion and scale inhibitor γ -gamma polyglutamic acid (10 mg L −1 )/hydrolysed polymaleic anhydride (6 mg L −1 )/benzotriazole (4 mg L −1 ) was developed. Its scale and corrosion inhibition performances were evaluated by bubble experiments, rotary hanging-piece corrosion tests, electrochemical, dynamic simulation test and scanning electron microscope. The rates of scale inhibition and corrosion inhibition were 94·8 and 85·4%, respectively. Further, scanning electron microscope morphology displayed complete and smooth carbon steel specimen surface, which was taken from dosing system. These results demonstrated that the water treatment agent possessed excellent scale and corrosion inhibition performance, so it can protect equipment and piping in the industrial circulating cooling water system.